Mikhail Bakhtin and Literary Life of Remote National Territories - S. A. Dubrovskaya; E. G. Maslova; L. Hui (Научный диалог)
The relevance of this study is underscored by the necessity to examine episodes from M. M. Bakhtin's scholarly biography within new contexts, particularly through the lens of postcolonial theory. This article demonstrates the productivity of integrating traditional historical-biographical paradigms with post-imperial/non-imperial interpretative methods. Utilizing under-researched materials from Bakhtin's time in Kustanai and Saransk during the 1930s, the authors trace the scholar's engagement with the life of national peripheries and identify traces of this experience in his works. It is noted that Bakhtin's return to Saransk in 1945 aligns with a trajectory from the “metropolis of culture” to the “province of experience.” As evidenced by cited archival documents, contemporaneous accounts, and local periodicals, Bakhtin emerges as a central figure not only in the pedagogical but also in the literary and cultural life of Mordovia. His name is associated with various activities — ranging from joint meetings with his department and representatives of the Writers' Union of the Mordovian ASSR to numerous seminars featuring talks with young writers, Mordovian authors, dramatic theater actors, and others. Special attention is given to previously unknown facts regarding Bakhtin's creative collaboration with playwright G. Ya. Merkushkin during the latter's work on the play “The Road of Life.”